The global status of nursing research on hemodialysis: A bibliometric and visualized analysis - Wang, Yufen; Yang, Luhuan; Lei, Yunhong (Lippincott Williams and Wilkins, 2024)
BACKGROUND: Hemodialysis (HD)-related nursing research has been growing over the past 2 decades, providing critical insights into improving patient care and outcomes. This study aimed to visualize the hotspots and emerging frontiers in HD-related nursing research, offering valuable references for future studies. METHODS: A bibliometric analysis was conducted on publications related to HD nursing research from the Web of Science Core Collection database, spanning the years 2002 to 2023, and the characteristics of literature such as authors, co-cited authors, countries, research institutions, journal distribution, keywords, and cited literature were visually analyzed using CiteSpace and VOSviewer. RESULTS: A total of 1019 publications were included in this study. The major contributors to this field were the United States, China, and Australia. The University of Sao Paulo emerged as the most prolific institution. The principal contributors were the Nephrology Nursing Journal, followed by Journal of Renal Care and Journal of Clinical Nursing. The top 5 co-occurrence keywords included HD, quality of life, dialysis, chronic kidney disease, and end-stage renal disease. The burst detection of keywords showed that current research frontier trends were pain and validation. The top 5 largest clusters of cited references included research on systematic review research, nurse-led disease management program, family caregiver, end-stage renal disease, and self-care intervention. CONCLUSION: This study reveals productive authors, countries and institutions, research hotspots, and trends of HD-related nursing research over the past 2 decades, offering a comprehensive overview of this field worldwide.